Painted Wooden Plaques from the MacFarlane Collection: The Earliest Inuvialuit Graphic Art - Morrison, David (ARCTIC, 2009)
In the 1860s, fur trader Roderick MacFarlane amassed a large ethnographic and zoological collection from the western Canadian Arctic, mainly on behalf of the Smithsonian Institution. Among the many items collected are eight hand-sized wooden plaques bearing incised polychrome scenes of traditional Inuvialuit (Mackenzie Inuit) life. The earliest significant examples of Inuvialuit graphic art in existence, these pieces provide a unique perspective on Inuvialuit culture and history at a critical period: during the first generation of sustained European contact. Dans les années 1860, Roderick MacFarlane, commerçant en fourrures, a recueilli une grande collection d’objets ethnographiques et zoologiques de l’ouest de l’Arctique canadien, surtout au nom du Smithsonian Institution. Parmi les nombreux articles qu’il a recueillis se trouvent huit plaques format de poche portant des gravures polychromes de scènes représentant la vie traditionnelle des Inuvialuits (les Inuits du Mackenzie). Ces oeuvres représentent les premiers exemples importants d’art graphique des Inuvialuits et à ce titre, elles offrent une perspective unique sur la culture et l’histoire des Inuvialuits à une période critique : pendant la première génération de contact soutenu avec les Européens.